2023
DOI: 10.1111/ppl.13943
|View full text |Cite
|
Sign up to set email alerts
|

An R2R3 MYB transcription factor PsFLP regulates the symmetric division of guard mother cells during stomatal development in Pisum sativum

Abstract: MYB transcriptional regulators belong to one of the most significant transcription factors families in plants, among which R2R3‐MYB transcription factors are involved in plant growth and development, hormone signal transduction, and stress response. Two R2R3‐MYB transcription factors, FLP and its paralogous AtMYB88, redundantly regulate the symmetrical division of guard mother cells (GMCs), and abiotic stress response in Arabidopsis thaliana. Only one orthologue gene of FLP was identified in pea (Pisum sativum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…The Lus.scaffold70.240 gene is a homologue of the AtMYB88 gene of Arabidopsis thaliana , and the AtMYB88 gene can regulate the late division of stomatal cell lineage [ 58 ]. qRT-PCR showed that PsFLP , the homologous gene of AtMYB88 in Pisum sativum , was involved in the response of Pisum sativum to drought stress [ 59 ]. Lus.scaffold4.116 and Lus.scaffold144.21 are the homologous genes of the Arabidopsis thaliana MYB family TBP-like type genes— AT1G07540 and AT3G12560 ( Supplementary Table S5 )—which play an important role in regulating the structure and function of eukaryotic telomeres.…”
Section: Discussionmentioning
confidence: 99%
“…The Lus.scaffold70.240 gene is a homologue of the AtMYB88 gene of Arabidopsis thaliana , and the AtMYB88 gene can regulate the late division of stomatal cell lineage [ 58 ]. qRT-PCR showed that PsFLP , the homologous gene of AtMYB88 in Pisum sativum , was involved in the response of Pisum sativum to drought stress [ 59 ]. Lus.scaffold4.116 and Lus.scaffold144.21 are the homologous genes of the Arabidopsis thaliana MYB family TBP-like type genes— AT1G07540 and AT3G12560 ( Supplementary Table S5 )—which play an important role in regulating the structure and function of eukaryotic telomeres.…”
Section: Discussionmentioning
confidence: 99%